Podophyllotoxin mediates hepatic toxicity via the C5a/C5aR/ROS/NLRP3 and cGMP/PKG/mTOR axis in rats based on toxicological evidence chain (TEC) concept by phosphoproteomic analysis - Liu, Chuanxin; Huang, Xiaobin; Kong, Jiao; Li, Xuejiao; Wang, Yuming; Zhang, Fangfang; Duan, Jiajia (Ecotoxicology and environmental safety, 2025)
Podophyllotoxin (PPT), a highly active compound extracted from the rhizome of Dysosma versipellis (DV), has been used as an effective anti-cancer drug clinically since the 1950s. It possesses various biological activities, including antiviral and antitumor effects. However, its clinical application is severely limited due to its hepatotoxicity, and the underlying mechanisms remain unclear. This study aims to elucidate the mechanisms of PPT-induced hepatotoxicity using tandem quality tag (TMT) based quantitative proteomics and phosphoproteomics, providing potential targets and directions for developing new therapeutic strategies to facilitate the safe and rational use of podophyllotoxin in clinical settings. We employed a comprehensive assessment of PPT-induced hepatotoxicity based on the Toxicology Evidence Chain (TEC) concept, originally proposed by our research group in 2018. This approach involves a tiered search for evidence of Harmful Ingredients Evidence (HIE), Injury Phenotype Evidence (IPE), Adverse Outcomes Evidence (AOE), and Toxic Events Evidence (TEE) during the development of PPT-induced hepatotoxicity, thereby constructing a guiding toxicology evidence chain. Sprague-Dawley (SD) rats were administered 20 mg/kg PPT for 4 consecutive days (HIE). Indicators such as hepatic function, oxidative stress, inflammatory factors, as well as the histopathology of liver tissue were evaluated to assess liver damage and synthetic function (AOE). Proteomics and phosphoproteomics were conducted to systematically assess PPT-induced hepatotoxicity at the level of modified proteins and verify the molecular mechanisms of key molecular pathways (TEE1). Furthermore, in vitro THLE-2 cell models were used in conjunction with CCK8, immunofluorescence, and ELISA assays to validate cytotoxicity and its underlying mechanisms (TEE2). Our results showed that after 4 days of PPT administration at 20 mg/kg (HIE), serum levels of AST/ALT, TBA, TP, and ALB in SD rats were significantly increased (P < 0.05), indicating severe liver damage. SOD and T-AOC levels were significantly decreased (P < 0.05), suggesting an oxidative stress state. TNF-α levels were significantly elevated, while IL-10 and IL-3 levels were significantly reduced (P < 0.05), indicating strong activation of the inflammatory response in the liver. Histopathological examination revealed liver sinusoidal congestion in the liver tissue (AOE). Omics analysis revealed that hepatotoxicity primarily affected the complement-pyroptosis and cGMP-PKG-autophagy pathways. Western blot (WB) and RT-qPCR results showed significant upregulation of complement-pyroptosis pathway proteins (C5a, C5aR, NLRP3) and cGMP-PKG-autophagy pathway proteins (PKG, mTOR) in the PPT group (P < 0.05) (TEE1). In vitro cell experiments showed that PPT significantly reduced cell viability (P < 0.05) and increased the expression of proteins associated with pyroptosis and autophagy pathways, including ROS, NLRP3, PKG, and mTOR (P < 0.05) (TEE2). PPT activates the complement system through the C5a/C5aR/ROS/NLRP3 pathway and induces the formation of inflammasomes, promoting pyroptosis. Simultaneously, PPT activates the cGMP-PKG pathway, inhibiting autophagy and further accelerating pyroptosis, ultimately leading to hepatotoxicity. In conclusion, this study comprehensively revealed the underlying mechanisms of PPT-induced hepatotoxicity using the TEC concept. This approach transforms fragmented toxicity indicators into systematic evidence of toxicity, presenting a hierarchical progression of toxicity evidence and avoiding data accumulation in natural drug toxicology. Our findings represent a significant breakthrough in the elucidation of the mechanisms of hepatotoxicity induced by podophyllotoxin. [Display omitted] •Proteomics and phosphorylated proteomics show podophyllotoxin (PPT) liver damage.•PPT activates cell apoptosis through C3-C3a-C5a-C5aR-ROS-NLRP3 axis.•PPT inhibits autophagy through the cGMP-PKG-mTOR axis.•Autophagy further activates pyroptosis, thereby causing liver toxicity.•This study formed a relatively complete toxicological evidence chain (TEC) of PPT.